Rearrangement of pyrrolines derived from the Birch reduction of electron-deficient pyrroles: radical ring-expansion to substituted tetrahydropyridines. - Turner, P; Donohoe, T; Cousins, R (2004)
Access to the synthetically important tetrahydropyridine motif has been achieved by radical rearrangement of pyrrolines obtained from the Birch reduction of electron-deficient pyrroles.